2015
DOI: 10.1080/01635581.2016.1115094
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate exerts chemoprevention of experimentally induced mammary tumorigenesis by suppression of cell proliferation and induction of apoptosis

Abstract: Breast cancer is the second leading cause of cancer-related death in women in the United States and discovery and development of safe chemopreventive drugs is urgently needed. The fruit pomegranate (Punica granatum) is gaining importance because of its various health benefits. This study was initiated to investigate chemopreventive potential of a pomegranate emulsion (PE) against 7,12-dimethylbenz(a)anthracene (DMBA) rat mammary carcinogenesis. The animals were orally administered with PE (0.2-5.0 g/kg), start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 57 publications
10
42
0
Order By: Relevance
“…In this review paper, we clearly summarized significantly higher cancer risk reduction activity in natural phyto-complexes when compared to isolated molecules [1]. Finally, significant (in many cases robust) chemopreventive effectiveness of various plant whole foods (dark fruits, herbs) in mammary carcinogenesis in female rats has also been described by other authors [46][47][48][49]. The translation of data from animal studies (such as daily doses of plant foods suitable for humans or effective plasma levels of plant metabolites) to clinical practice is not easily applicable.…”
Section: Discussionmentioning
confidence: 68%
“…In this review paper, we clearly summarized significantly higher cancer risk reduction activity in natural phyto-complexes when compared to isolated molecules [1]. Finally, significant (in many cases robust) chemopreventive effectiveness of various plant whole foods (dark fruits, herbs) in mammary carcinogenesis in female rats has also been described by other authors [46][47][48][49]. The translation of data from animal studies (such as daily doses of plant foods suitable for humans or effective plasma levels of plant metabolites) to clinical practice is not easily applicable.…”
Section: Discussionmentioning
confidence: 68%
“…This observation is in accordance with several studies, which showed that DMBA alters the normal process of mammary gland differentiation. 18,36,46,47 Daucosterol reduced spleen, liver, lungs, and kidneys wet weights to the normal values compared to the DMBA group. These organs are indicators of toxicity when testing natural substances.…”
Section: T a B L Ementioning
confidence: 82%
“…. There is abundant research in animal models that highlights a significant role of polyphenols and polyphenol‐rich plant extracts in the prevention of breast cancer, including resveratrol, ellagic acid, berries, pomegranate, and citrus flavanones . However, this evidence remains elusive in humans.…”
Section: Introductionmentioning
confidence: 99%